MENTAL HEALTH OF YOUTH IN THE COVID CAPITAL OF INDIA: MAHARASHTRA - Dr. Juhi Deshmukh; Prof. B. R. Shejwal; Prof. Satishchandra Kumar; Prof. Dave Sookhoo; Dr. Aparna Satpute; Mr. Abhijeet Chore; Ms. Shweta Sahasrabuddhe (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
The Coronavirus Disease-2019 outbreak brought along a set of unprecedented challenges affecting virtually all domains of human life. The mental health of the youth has been one major area of concern. There are various factors that determined how the pandemic was received by the diverse population of the country. This study is a postlude to an already conducted primary study and throws light on the status of the mental health of youth in one of the country's worst affected states, Maharashtra. A sample of 567 youth was studied from various parts of Maharashtra and multiple streams of education representing different genders, family structures and social support. This paper is an enquiry in the levels of Anxiety, Depression, Stress and Well-being among youth from various backgrounds. In the context of the Pandemic, major mental health consequences were felt in the country; youth taking higher education were exposed to ‘a new normal’ of online education and uncertainty. Despite the fact that mental distress like anxiety, depression and stress is a prevalent theme among this population, there has been a dearth of formal records of the same. This research uses a sequential mixed method design wherein the participants of the study were interviewed and an account of their experiences during the pandemic was documented through individual interviews and thematic content analysis. The current study aims to bridge this gap and pose an inquiry about the reasons for the same, so that better sensitization and mitigation strategies may be developed and implemented at a policy level to guard the mental well-being of our most valuable resource “youth”. The obtained results show an interesting trend among the population pertaining to their area of residence, availability of space, gender differences, the type of family and perceived social support. Significant differences were obtained for the scores on Depression, Anxiety, Stress and Well Being. The results obtained could go a long way in bolstering mental health training modules. Relevant modifications could be done to existing Disaster Management Policies to ensure holistic effectiveness of the program. Additional findings are also discussed.